THE METHODICAL ASPECTS OF THE USE OF ENVIRONMENTAL EFFECT RISK ASSESSMENT METHODOLOGY OF PUBLIC HEALTH IN UKRAINE AND RUSSIA - Scherban, N.G.; МyasoedovV.V.; ShevchenkoЕ.А.; Savchenko, V.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
On the basis of system analysis and evaluation of our textbook data, published data, as well as regulatory and procedural documents the problem of using of risk assessment techniques to public health under the influence of unfavorable factors of environment in environmental-hygienic studies as well as in environmental and health practice in Ukraine and Russia was disclosed. It was concluded that lack of effective implementation and practical application of this methodology in Ukraine exists. Recommendations were developed to optimize the situation, in particular through the formation of system of personnel training and Ukrainian and regional «Associations of risk assessment to human health».